2021
DOI: 10.3390/ijerph18126512
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Fitness Is Associated with Success in Sport for Elite Female, but Not Male Tennis Players

Abstract: Background: The purpose of the study was to examine whether neuromuscular fitness contributes significantly to the success of eAlite junior tennis players of differing ages and sexes. Methods: The 160 participants, who were elite Hungarian junior tennis players (aged 11–17), were separated into four groups within this study, and 10 different types of field tests were used. Results: A moderate significant correlation was found between the results of the 5 m run (r = −0.42; r = −0.45), standing long jump (r = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…Regarding posterior flexibility, previous research observed similar differences between genders in table tennis players [ 36 ], in professional padel players [ 9 ] and in tennis players of similar ages [ 57 ]. Women players present greater flexibility compared to men, possibly due to the anatomical design of the bony structures of the hips and pelvis (pelvic retroversion) and hormonal regulation (oestrogens) that generates less stiffness [ 58 ].…”
Section: Discussionmentioning
confidence: 83%
“…Regarding posterior flexibility, previous research observed similar differences between genders in table tennis players [ 36 ], in professional padel players [ 9 ] and in tennis players of similar ages [ 57 ]. Women players present greater flexibility compared to men, possibly due to the anatomical design of the bony structures of the hips and pelvis (pelvic retroversion) and hormonal regulation (oestrogens) that generates less stiffness [ 58 ].…”
Section: Discussionmentioning
confidence: 83%
“…Spider run is a tennis-specific sprint test (also use in soft tennis), which was developed by the Japan Tennis Association (2005; Figure 1 , right). It measures the on-court movement of the athlete, including speed, coordination and the ability to accelerate and brake over short distances, in five directions and in three different stances, which is used as an essential agility index of players’ on-court performance ( Kuroda et al, 2015 , 2017 ; Dobos et al, 2021 ). Participants were requested to run from the center of the baseline to a marked point and back; then, they would repeat this until five different directions were completed.…”
Section: Methodsmentioning
confidence: 99%
“…In tennis, various components of physical fitness play an important role. On the one hand, the average duration for scoring a point is less than 3–10 s [ 1 , 2 ] with sprints of 8–15 m (i.e., speed) and 3–4 directional changes (i.e., agility) taking place during rallies [ 3 5 ]. On the other hand, a match can last up to five hours, which shows the importance of tennis-specific endurance [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the average duration for scoring a point is less than 3–10 s [ 1 , 2 ] with sprints of 8–15 m (i.e., speed) and 3–4 directional changes (i.e., agility) taking place during rallies [ 3 5 ]. On the other hand, a match can last up to five hours, which shows the importance of tennis-specific endurance [ 1 , 2 ]. Further, different components of strength (e.g., lower extremity muscle power) are important to perform tennis-specific footwork and explosive strokes during rallies [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation